Chinese Adolescents’ Emotional Intelligence, Perceived Social Support, and Resilience—The Impact of School Type Selection - Chen, Shitao (Frontiers in Psychology, 2019)
Choosing a school that can best assist children’s development has become one of the major concerns of Chinese parents. To categorize schools by where students stay after school, this paper consider boarding schools or day schools as two major school types. This study examined the relationships among emotional intelligence (EI), perceived social support (from friends and family) and resilience for 493 Chinese adolescents (male=249, female=244; Mean age = 13.9, SD=0.71), and investigated how school type difference impacts these relationships. This research first used a moderator analysis to investigate the effects of trait emotional intelligence on resilience by perceived social support from family and friends, respectively. Results show that social support from family was non-significant, while support from friends was significant in moderating the relationship between EI and resilience. Further, a moderated moderation analysis was used to understand if moderation by school type of perceived social support differs in the effect of trait EI on resilience. Results indicated that the magnitude of the moderation by social support from friends depended on school type. For students who have lower perceived friend support, boarding school experiences provided a stronger positive relationship between trait EI and resilience than day school experience. Ways to enhance students’ perceived social support are discussed, along with the limitations of the current research and recommendations for future research.